Hypoxia and Ischemia Promote a Maladaptive Platelet Phenotype. Issue 7 (July 2018) - Cameron, Scott J.; Mix, Doran S.; Ture, Sara K.; Schmidt, Rachel A.; Mohan, Amy; Pariser, Daphne; Stoner, Michael C.; Shah, Punit; Chen, Lijun; Zhang, Hui; Field, David J.; Modjeski, Kristina L.; et al.
Abstract : Objective—: Reduced blood flow and tissue oxygen tension conditions result from thrombotic and vascular diseases such as myocardial infarction, stroke, and peripheral vascular disease. It is largely assumed that while platelet activation is increased by an acute vascular event, chronic vascular inflammation, and ischemia, the platelet activation pathways and responses are not themselves changed by the disease process. We, therefore, sought to determine whether the platelet phenotype is altered by hypoxic and ischemic conditions. Approach and Results—: In a cohort of patients with metabolic and peripheral artery disease, platelet activity was enhanced, and inhibition with oral antiplatelet agents was impaired compared with platelets from control subjects, suggesting a difference in platelet phenotype caused by the disease. Isolated murine and human platelets exposed to reduced oxygen (hypoxia chamber, 5% O2 ) had increased expression of some proteins that augment platelet activation compared with platelets in normoxic conditions (21% O2 ). Using a murine model of critical limb ischemia, platelet activity was increased even 2 weeks postsurgery compared with sham surgery mice. This effect was partly inhibited in platelet-specific ERK5 (extracellular regulated protein kinase 5) knockout mice. Conclusions—: These findings suggest that ischemic disease changes the platelet phenotype and alters platelet agonist responses because of changes in the expression of signal transduction pathway proteins. Platelet phenotype and function should, therefore, be better characterized in ischemic and hypoxic diseases to understand the benefits and limitations of antiplatelet therapy. Abstract : Supplemental Digital Content is available in the text.